Silvicultural performance of Plathymenia reticulata with phosphorous addition in Forest Atlantic, Brazil - Araújo, Emanuel França; Carreço, Ray Luiz Babilon; Silva, Jeferson Pereira Martins; Menezes, Marília Braz de Carvalho; Bighi, Kelly Nery; Gonçalves, Elzimar de Oliveira; Caldeira, Marcos Vinicius Winckler; Godinho, Tiago de Oliveira (Instituto de Ecología, A.C., 2021)
The objective of this study was to analyse the initial medium-term growth of a P. reticulata settlement under different phosphorus doses. The experiment was carried out in an area of Atlantic Forest, Sooretama, Northern Espírito Santo State, Brazil. Five doses of P per each tree (0 g, 27 g, 47 g, 67 g and 87 g) were tested in a randomized block design with three replicates and 18 plants per plot. At 3 months, 9 months and 15 months, height and diameter were measured at the soil level. At 36 months height, diameter at breast height, survival, basal area, and nutritional evaluation of the trees were measured. A logistic model was also used to model the growth in height of individual trees and a logistic model considering fixed effects and mixed form (fixed and random effects), in order to verify if the inclusion of the random effect (tree) would result in gains in terms of accuracy in the estimation of the future height of P. reticulata trees. The species presents potential for use in reforestation programs under edaphoclimatic conditions tested and under similar conditions. The species was not very demanding in P, and the addition of this nutrient promotes negative effects on its growth in the short and medium term. Regarding the model of growth in height, the logistic model adjusted in the mixed form showed to be superior to the traditional adjustment.